Analisis Pemilihan Moda Angkutan Umum atau Pribadi Pekerja Mobilitas Non-Permanen di Sepuluh Wilayah Metropolitan Indonesia - Chotib, Chotib (Journal of Regional and Rural Development Planning, 2019)
There are several types of non-permanent mobility which are generally related to location difference between places of residence and places of work. Non-permanent mobility consists of commuting, circular, and seasonal migration. Commuting is a type of non-permanent mobility where a person works in a different place from his residence, he/she leaves in the morning and returns in the afternoon or evening every day. Circular is a type of non-permanent mobility where a person lives in a workplace (which is different from his place of residence) for less than three months but more than one day. Whereas seasonal migrantion is a type of non-permanent mobility where the person lives in the workplace (destination area) between 3 and 6 months. This study aims to identify the probability of public transportation use by workers, both as movers and stayers, in ten metropolitan regions in Indonesia, namely Mebidang (Medan metropolitan area), Palapa (Padang metropolitan area), Patungraya Agung (Palembang metropolitan area), Jabodetabek (Greater Jakarta), Bandung Raya (Bandung metropolitan area), Kedungsepur (Semarang metropolitan area), Gerbangkertosusila (Surabaya metropolitan area), Sarbagita (Denpasar metropolitan area), Banjar Bakula (Banjarmasin metropolitan area), and Maminasata (Makassar metropolitan area). The results of the analysis with Binary Logistic Regression on the Sakernas 2017 data shows that the probability of using public transportation varies according to individual characteristics, patterns of mobility and varies over Metropolitan Areas.